Quality requirements assessed in the supply of raw milk by Brazilian dairy - Satolo, Eduardo Guilherme [UNESP]; Ferreira, Bruna Maria Zumkeller [UNESP]; Mac-Lean, Priscilla Ayleen Bustos [UNESP]; Gotardi, Juliani Elis Duarte [UNESP]; Santos, Isabela Garcia Mendes de Araujo [UNESP] (IGI Global, 2023)
In Brazil the quality required by dairy is established through regulations 76 and 77. This chapter aims to identify the technical quality requirements evaluated in the supply of raw milk by dairy companies located in the state of São Paulo. Using the voice of the customer (VOC) it is possible to identify compatible internal requirements to drive the improvement process. The results indicate the need for actions to raise awareness of the agents involved in the dairy production chain. First, the role of the dairy, in understanding that the legal parameters must be measured and controlled, given the perishability of milk. Second, producers and dairies must understand that superior milk quality results in better quality products, and to achieve this, the actions carried out on the property and evaluated parameters must be worked out through action plans. Finally, that action plans will only be successful if they are carried out in partnership with the rural producer, understanding that the gain will occur if everyone works collectively and not individually along the production chain.